1999
DOI: 10.1177/0739986399212001
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence as a Human Rights Issue: The Case of Immigrant Latinos

Abstract: Using the writings of the late social psychologist Ignacio Martín-Baró and other Latin American and Latino social scientists as a framework, this article examines the issue of domestic violence from a human rights perspective. As suggested by these writers, the antecedents, dynamics, and effects of domestic abuse are explored, bringing to bear the historical, philosophical, cultural, social, spiritual, and political realities of Latino immigrants in the United States. From this ecological perspective, universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
157
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 17 publications
4
157
0
2
Order By: Relevance
“…Indeed, some researchers suggest that the childhood socialization of Latinas, the message that marriage is of utmost importance and is essential to identity, and the expectation that women should be submissive, may all increase the frequency and severity of intimate partner violence among Latino couples and augment women's tolerance of abuse (Perilla, 1999). Champion (1996) found that the abused Mexican American women in her sample were more traditional regarding gender role expectations than non-abused women.…”
Section: Cultural Factors Associated With Mexican-origin Women's Respmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, some researchers suggest that the childhood socialization of Latinas, the message that marriage is of utmost importance and is essential to identity, and the expectation that women should be submissive, may all increase the frequency and severity of intimate partner violence among Latino couples and augment women's tolerance of abuse (Perilla, 1999). Champion (1996) found that the abused Mexican American women in her sample were more traditional regarding gender role expectations than non-abused women.…”
Section: Cultural Factors Associated With Mexican-origin Women's Respmentioning
confidence: 99%
“…Also, because of machismo, male sexual jealousy may be viewed as a legitimate reason to abuse one's wife (Morash et al, 2000;Perilla, 1999).…”
Section: Cultural Factors Associated With Mexican-origin Women's Respmentioning
confidence: 99%
See 2 more Smart Citations
“…To these may be added approaches in North America, especially those that have focussed on work with populations who owe their presence to past and present imperialisms (African USAmericans, Latinos) and native North Americans (e.g. Perilla, 1999 Harnessing of university resources to promote work on things that matter to people and groups from these areas.…”
Section: Community Social Psychologymentioning
confidence: 99%